Einblicke in die apophatische und mystische Bedeutung der theologischen Anthropologie von André Scrima - Huian, Georgiana (Review of ecumenical studies, 2020)
This article investigates two fundamental dimensions of André Scrima's anthropology: his emphasis on the incomprehensibility of the human being, and his interest for the mystical life in spiritual experience. The author intertwines these aspects in a range of topics with the aim of approaching the nature of the human being, such as the access to God as presence, the deification or transfiguration of the human being, and the iconic character of human existence. I analyze the use of such terms like "participation" and "mixture," as well as the imagery that depicts the union of the human and the divine. Finally, I underline the spiritual importance of the nomad as figure and hospitality as virtue, and interpret them in terms of human itinerancy and God's mystical dwelling in the human person.